GABAergic signaling to astrocytes in the prefrontal cortex sustains goal-directed behaviors - Mederos, Sara; Sánchez-Puelles, Cristina; Esparza, Julio; Valero, Manuel; Ponomarenko, Alexey; Perea, Gertrudis (Nature Neuroscience, 2020)
GABA interneurons play a critical role in higher brain functions. Astrocytic glial cells interact with synapses throughout the whole brain and are recognized as regulatory elements of excitatory synaptic transmission. However, it is largely unknown how GABAergic interneurons and astrocytes interact and contribute to stable performance of complex behaviors. Here, we found that genetic ablation of GABAB receptors in medial prefrontal cortex astrocytes altered low-gamma oscillations and firing properties of cortical neurons, which affected goal-directed behaviors. Remarkably, working memory deficits were restored by optogenetic stimulation of astrocytes with melanopsin. Furthermore, melanopsin-activated astrocytes in wild-type mice enhanced the firing rate of cortical neurons and gamma oscillations, as well as improved cognition. Therefore, our work identifies astrocytes as a hub for controlling inhibition in cortical circuits, providing a novel pathway for the behaviorally relevant midrange time-scale regulation of cortical information processing and consistent goal-directed behaviors.
CRIS-Team Scopus Importer:2020-12-18